On the application of sliding mode control to indirectly coupled photovoltaic-electrolyzer systems used in the production of clean energy - (:unkn) unknown (Elsevier BV, 2024)
To improve the performance of photovoltaic-electrolyzer (PV-EL) systems, it is key to operate them at the right operating conditions, not only at design point but also at off-design. In addition, when directly coupling a PV system to an EL one, an ideal ...
Keywords: Control por modo deslizante; Energía fotovoltaica